Pembaharuan Fitur Aplikasi Laporan Keuangan Berbasis Excel Untuk Umkm Ayam Kefrec & Coffeeshop Shine And Smile Car Wash - Muhammad Abdul Karim; Imam Subaweh (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This research aims to develop and modify a Microsoft Excel-based financial reporting application by adding input forms for accounts payable and receivable transactions to facilitate financial management for MSMEs, particularly Ayam KeFreC & Coffeeshop Shine and Smile Car Wash. The research method used is developmental research, involving the stages of needs analysis, design, implementation, and application testing. Data analysis techniques include direct observation, interviews, and testing of application functions as well as data input accuracy. The collected data were analyzed both descriptively and quantitatively to assess the application's effectiveness, ease of use, and practicality. The results indicate that the developed application successfully facilitates structured and automated financial transaction recording through the use of macros and input forms for payables and receivables. However, there are still shortcomings in the user interface and library system, which need improvement to make the application more user-friendly and suitable for long-term use. In conclusion, the application has proven effective in helping MSMEs manage their finances more efficiently and accurately, and it holds development potential to enhance business performance in the digital era.